Comparison of seed germination and early seedling growth responses to salinity and temperature of the halophyte Chloris virgata and the glycophyte Digitaria sanguinalis. (5th December 2012) - Zhang, H. X.; Zhou, D. W.; Tian, Y.; Huang, Y. X.; Sun, Z. W.
Abstract: Salinization is an increasing land degradation issue in the Songnen Grassland of northern China. Effects of salinity and temperature on seed germination and seedling growth of Chloris virgata, a promising halophyte, and Digitaria sanguinalis, a widespread glycophyte were examined in six soil solutions (0, 50, 100, 150, 200 and 250 mm NaCl) and four temperatures (15, 20, 25 and 30°C). Germination percentages and rates of both species decreased significantly at higher salinities, but ungerminated seeds can recover germination upon supply of distilled water. Radicle length, seedling height and the total dry weight of both species generally decreased in a concentration‐dependent manner at 20°C and above as the salinity increased. However, at 15°C, the salt‐treated seedlings showed decreases with a similar magnitude for different salinities. Low salinities seem to stimulate germination and seedling growth of C. virgata compared with the control treatment. Both species were more sensitive to salinity during the seedling stage than the germination stage. Digitaria sanguinalis from the saline Songnen Grassland region seems to develop a halophyte‐like adaptive strategy to some extent. However, C. virgata may still dominate most hyperhaline areas due to its higher salt tolerance.